2021
DOI: 10.3390/ijms222011164
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Protein Phosphatase 2A Regulates Cell Survival Mechanisms in Influenza A Virus Infection

Abstract: Influenza A viruses (IAVs) are respiratory pathogens that are able to hijack multiple cellular mechanisms to drive their replication. Consequently, several viral and cellular proteins undergo posttranslational modifications such as dynamic phosphorylation/dephosphorylation. In eukaryotic cells, dephosphorylation is mainly catalyzed by protein phosphatase 2A (PP2A). While the function of kinases in IAV infection is quite well studied, only little is known about the role of PP2A in IAV replication. Here, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…In the RHTiB cells, infection by TiLV prompted a distinct cellular response compared to the E-11 cells. Specifically, at 10 mpi, there was a suppression of the protein PPP2R2A, an enzyme involved in the dephosphorylation of intracellular proteins 61 , and MTHFD2, which plays a role in RNA metabolism and translation 62 . Previous research has demonstrated that the downregulation of protein phosphatase leads to cell senescence in aging zebrafish neuronal cells 63 , and the suppression of MTHFD2 has been linked to cell death in infectious hematopoietic necrosis virus (IHNV)-infected zebrafish larvae 64 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the RHTiB cells, infection by TiLV prompted a distinct cellular response compared to the E-11 cells. Specifically, at 10 mpi, there was a suppression of the protein PPP2R2A, an enzyme involved in the dephosphorylation of intracellular proteins 61 , and MTHFD2, which plays a role in RNA metabolism and translation 62 . Previous research has demonstrated that the downregulation of protein phosphatase leads to cell senescence in aging zebrafish neuronal cells 63 , and the suppression of MTHFD2 has been linked to cell death in infectious hematopoietic necrosis virus (IHNV)-infected zebrafish larvae 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that the downregulation of protein phosphatase leads to cell senescence in aging zebrafish neuronal cells 63 , and the suppression of MTHFD2 has been linked to cell death in infectious hematopoietic necrosis virus (IHNV)-infected zebrafish larvae 64 . Thus, the suppression of these proteins in infected RHTiB cells indicates that TiLV may inhibit host cell replication and metabolism early in the infection process, which facilitates viral entry and replication, as seen with other viruses, such as influenza A virus, hepatitis B, and Epstein-Barr virus (EBV) 61,[65][66][67] . Additionally, at 10 mpi, the TiLV-infected RHTiB cells showed inhibition of cytoskeletal proteins, including BCAS3, which controls the direction of cell migration 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Both the paper by Harris and colleges and the paper by Gerlt and coworkers deal with the respiratory pathogen IAV [ 9 , 10 ]. The host innate immune response is essential to inhibit IAV replication.…”
mentioning
confidence: 99%
“…The age- and strain-dependent attenuation of the innate immune responses to IAV infection in mice reflects the phenotypic differences in infected young and old mice and suggests that the decline in innate immunity functions in elderly may contribute to the increased susceptibility to influenza [ 9 ]. Gerlt and colleges studied the role of protein phosphatase 2A (PP2A) in IAV replication [ 10 ]. By using RNA interference-mediated knockdown of the catalytic subunit of PP2A or the inhibition of PP2A by okadaic acid, the authors found that PP2A exhibited a supportive role in IAV replication in cells by increasing cell survival after viral infection.…”
mentioning
confidence: 99%